INTOLERANSI TERSELUBUNG DALAM BUDAYA SEKOLAH NEGERI: ANALISIS PRAKTIK DISKRIMINASI SIMBOLIK TERHADAP SISWA MINORITAS - Jecsonius Robinson (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
This study aims to analyze hidden intolerance within public school culture and reveal the forms of symbolic discrimination experienced by minority students in everyday school life. The research focuses on the dominance of majority culture, symbolic discrimination practices, hidden curriculum, psychosocial experiences of minority students, and the role of teachers and schools in managing diversity. This study employed a qualitative approach using a case study design. Data were collected through participatory observation, in-depth interviews, and documentation involving minority students, teachers, counseling teachers, and school administrators. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that intolerance in public schools does not always appear in the form of overt discrimination, but is reproduced latently through school culture, social symbols, institutional habits, and communication patterns that predominantly represent the majority group. Symbolic discrimination was found in the form of religious jokes, social labeling, neglect of minority students’ opinions, social segregation, and the normalization of homogeneous school culture. These conditions affect minority students’ learning comfort, self confidence, and social participation within the school environment. The novelty of this study lies in its analysis of hidden intolerance through the perspectives of symbolic discrimination and hidden curriculum in public school culture, which remains underexplored in the Indonesian educational context. This study contributes to the development of multicultural education studies, inclusive school culture, and educational policies that are more responsive to student diversity. ABSTRAK Penelitian ini bertujuan untuk menganalisis bentuk intoleransi terselubung dalam budaya sekolah negeri serta mengungkap praktik diskriminasi simbolik yang dialami siswa minoritas di lingkungan sekolah. Fokus penelitian diarahkan pada dominasi budaya mayoritas, praktik diskriminasi simbolik, hidden curriculum, pengalaman psikososial siswa minoritas, serta peran guru dan sekolah dalam mengelola keberagaman. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Teknik pengumpulan data dilakukan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi terhadap siswa minoritas, guru, guru bimbingan dan konseling, serta pihak sekolah. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa intoleransi di sekolah negeri tidak selalu muncul dalam bentuk diskriminasi terbuka, tetapi direproduksi secara laten melalui budaya sekolah, simbol sosial, kebiasaan institusi, dan pola komunikasi yang lebih merepresentasikan praktik laten. Praktik diskriminasi simbolik ditemukan dalam bentuk candaan bernuansa agama, pelabelan sosial, pengabaian pendapat siswa minoritas, segregasi sosial, serta pembiasaan budaya sekolah yang homogen. Kondisi tersebut berdampak terhadap kenyamanan belajar, rasa percaya diri, dan partisipasi sosial siswa minoritas dalam lingkungan sekolah. Novelty penelitian ini terletak pada analisis intoleransi terselubung melalui perspektif diskriminasi simbolik dan hidden curriculum dalam budaya sekolah negeri yang masih jarang dikaji dalam konteks pendidikan Indonesia. Penelitian ini berkontribusi dalam pengembangan kajian pendidikan multikultural, budaya sekolah inklusif, dan kebijakan pendidikan yang lebih sensitif terhadap keberagaman peserta didik.